Effect of minimalist and maximalist shoes on impact loading and footstrike pattern in habitual rearfoot strike trail runners: an in-field study - Mo, S.; Chan, Z. Y. S.; Lai, K. K. Y.; Chan, P. P.-K.; Wei, R. X.-Y.; Yung, P. S.-H.; Shum, G.; Cheung, R. T.-H. (European Journal of Sport Science, 2021)
Running-related injuries among trail runners are very common and footwear selection may modulate the injury risk. However, most previous studies were conducted in a laboratory environment. The objective of this study was to examine the effects of two contrasting footwear design, minimalist (MIN) and maximalist shoes (MAX), on the running biomechanics of trail runners during running on a natural trail. Eighteen habitual rearfoot strike trail runners completed level, uphill and downhill running at their preferred speeds in both shod conditions. Peak tibial acceleration, strike index and footstrike pattern were compared between the two footwear and slopes. Interactions of footwear and slope were not detected for all the selected variables. There was no significant effect from footwear (F=1.23, p=0.27) and slope (F=2.49, p=0.09) on peak tibial acceleration and there was no footwear effect on strike index (F=3.82, p=0.056). A significant main effect of slope on strike index (F=13.24, p<0.001) was found. Strike index during uphill running was significantly greater (i.e., landing with a more anterior foot strike) when compared with level (p<0.001, Cohen`s d=1.72) or downhill running (p<0.001, Cohen`s d=1.44) in either MIN or MAX. The majority of habitual rearfoot strike runners switched to midfoot strike during uphill running while maintaining a rearfoot strike pattern during level or downhill running. In summary, wearing either one of the two contrasting footwear (MIN or MAX) demonstrated no effect on impact loading and footstrike pattern in habitual rearfoot strike trail runners running on a natural trail with different slopes.